Neutron-capture elements in dwarf galaxies III: a homogenized analysis of 13 dwarf spheroidal and ultra-faint galaxies - Reichert, Marjolein; Hansen, Camilla Juul; Hanke, Michael; Skuladottir, A.; Arcones Segovia, Almudena; Grebel, Eva K. (Astronomy and astrophysics, 2020)
Context. We present a large homogeneous set of stellar parameters and abundances across a broad range of metallicities, involving 13 classical dwarf spheroidal (dSph) and ultra-faint dSph (UFD) galaxies. In total, this study includes 380 stars in Fornax, Sagittarius, Sculptor, Sextans, Carina, Ursa Minor, Draco, Reticulum II, Bootes I, Ursa Major II, Leo I, Segue I, and Triangulum II. This sample represents the largest, homogeneous, high-resolution study of dSph galaxies to date.Aims. With our homogeneously derived catalog, we are able to search for similar and deviating trends across different galaxies. We investigate the mass dependence of the individual systems on the production of alpha-elements, but also try to shed light on the long-standing puzzle of the dominant production site of r-process elements.Methods. We used data from the Keck observatory archive and the ESO reduced archive to reanalyze stars from these 13 classical dSph and UFD galaxies. We automatized the step of obtaining stellar parameters, but ran a full spectrum synthesis (1D, local thermal equilibrium) to derive all abundances except for iron to which we applied nonlocal thermodynamic equilibrium corrections where possible.Results. The homogenized set of abundances yielded the unique possibility of deriving a relation between the onset of type Ia supernovae and the stellar mass of the galaxy. Furthermore, we derived a formula to estimate the evolution of alpha-elements. This reveals a universal relation of these systems across a large range in mass. Finally, we show that between stellar masses of 2.1x10(7) M-circle dot and 2.9x10(5) M-circle dot, there is no dependence of the production of heavy r-process elements on the stellar mass of the galaxy.Conclusions. Placing all abundances consistently on the same scale is crucial to answering questions about the chemical history of galaxies. By homogeneously analyzing Ba and Eu in the 13 systems, we have traced the onset of the s-process and found it to increase with metallicity as a function of the galaxy's stellar mass. Moreover, the r-process material correlates with the alpha-elements indicating some coproduction of these, which in turn would point toward rare core-collapse supernovae rather than binary neutron star mergers as a host for the r-process at low [Fe/H] in the investigated dSph systems.